2021
DOI: 10.47836/pjssh.29.s3.23
|View full text |Cite
|
Sign up to set email alerts
|

Language Education for Orang Asli Children in Malaysia

Abstract: Literacy among Orang Asli children is found to be well below the national average. This paper explores the connection between language learning and meaning-making and its relation to the problem of language education among Orang Asli children. In so doing, the paper shows that language learning should be situated within their environment. This paper uses the findings from the observation made in an exploratory case study of Temuan children aged 7–12 in an Orang Asli village in Selangor and their struggles with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This result was supported by Abdullah et al (2013), which concluded that Malaysian teaching pedagogy is a stereotype and fails to stimulate students' enthusiasm for attending school. Additionally, literacy in language learning among indigenous school pupils is found to be well below the national average (Letchamanan et al, 2021). Supported by Sawalludin et al (2020) that the attitude of indifference to education had caused the failure to improve the quality of education among indigenous school pupils.…”
Section: Literature Review Skills For Learning (The Way To Know)mentioning
confidence: 99%
“…This result was supported by Abdullah et al (2013), which concluded that Malaysian teaching pedagogy is a stereotype and fails to stimulate students' enthusiasm for attending school. Additionally, literacy in language learning among indigenous school pupils is found to be well below the national average (Letchamanan et al, 2021). Supported by Sawalludin et al (2020) that the attitude of indifference to education had caused the failure to improve the quality of education among indigenous school pupils.…”
Section: Literature Review Skills For Learning (The Way To Know)mentioning
confidence: 99%
“…The dropout rate among school children is also indecisive. [20,21] Consequently, the HL rate among the population living in PAs is affected. They cannot comprehend health information well or use it effectively in their daily life.…”
Section: Introductionmentioning
confidence: 99%